Transcription of a vaccinia virus late promoter template: requirement for the product of the A2L intermediate-stage gene. - Passarelli, A L (1996)
Evidence is presented that a 26-kDa protein encoded by the vaccinia virus A2L open reading frame, originally shown to be one of three intermediate-stage genes that together can transactivate late-stage gene expression in transfection assays (J. G. Keck, C. J. Baldick, and B. Moss, Cell 61:801-809, 1990), is required for in vitro transcription of a template with a late promoter. The critical step in this analysis was the preparation of an extract containing all the required factors except for the A2L protein. This extract was prepared from cells infected with a recombinant vaccinia virus expressing the bacteriophage T7 RNA polymerase in the presence of the DNA synthesis inhibitor cytosine arabinoside and transfected with plasmids containing the two other known transactivator genes, A1L and G8R, under T7 promoter control. Reaction mixtures made with extracts of these cells had background levels of late transcription activity, unless they were supplemented with extracts of cells transfected with the A2L gene. Active transcription mixtures were also made by mixing extracts from three sets of cells, each transfected with a gene (A1L, A2L, or G8R) encoding a separate factor, indicating the absence of any requirement for their coexpression. To minimize the possibility that the A2L protein functions indirectly by activating another viral or cellular protein, this gene was expressed in insect cells by using a baculovirus vector. The partially purified recombinant protein complemented the activity of A2L-deficient cell extracts. Recombinant A1L, A2L, and G8R proteins, all produced in insect cells, together complemented extracts from mammalian cells containing only viral early proteins, concordant with previous in vivo transfection data.